Smartphone Digital Forensics: A Decade of Legal Insights - Archintya, Noviana; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This dataset, acquired from Lens.org, serves as a valuable resource for researchers delving into the nexus of "Digital Forensics" and "Smartphones." The search, initiated with 1,627 documents, underwent meticulous filtering, narrowing it down to 961 journal articles, all published within the ten-year span from 2012 to 2022 and centered around the subject of "Law." Notably, the top contributing institution during this period was Universitas Ahmad Dahlan with 40 documents. The dataset showcases the most prolific year in 2019 with 175 journal articles, primarily exploring Computer Science, particularly in the domain of "Computer Science," where it offers a substantial 1,060 documents. The dataset also highlights the active institutions and authors, enabling in-depth analysis and further research on digital forensics in the context of smartphones. Highlight: Comprehensive Dataset: This dataset offers a wealth of information for researchers exploring the intersection of digital forensics and smartphones, streamlining the research process. Rigorous Filtering: Through precise filtering by document type, date range, and subject matter, the dataset ensures data relevance and accuracy. Research Avenues: Researchers can leverage this resource to gain insights into legal aspects of digital forensics in smartphone-related investigations, fostering further exploration and scholarly work. Keywords: Digital Forensics, Smartphones, Dataset, Legal Insights, Research